Final Subduction Processes of the Paleo‐Asian Ocean in the Alxa Tectonic Belt (NW China): Constraints From Field and Chronological Data of Permian Arc‐Related Volcano‐Sedimentary Rocks. Issue 6 (5th June 2018) - Song, Dongfang; Xiao, Wenjiao; Collins, Alan S.; Glorie, Stijn; Han, Chunming; Li, Yongchen
Abstract: The timing of final subduction and closure of the Paleo‐Asian Ocean (PAO) is controversial. Located in a key position within the southern Central Asian Orogenic Belt, the Alxa Tectonic Belt (ATB) provides a crucial window to evaluate the final subduction processes of the PAO. This study presents field and geochronological data for Permian volcano‐sedimentary rocks from the southwestern ATB. Field observations revealed a syntectonic unconformity between the Middle and Upper Permian strata. Detrital zircon U‐Pb analyses show a major peak at 273 Ma and a subordinate peak at 440 Ma for the Middle Permian sample. The Upper Permian samples show consistently unimodal age spectra with single peaks at 261 and 263 Ma, respectively. The Permian zircons from the analyzed samples yield predominately positive ε Hf ( t ) values, indicating major juvenile magmatic processes mixed with limited recycled Precambrian basement. The diagnostic zircon U‐Pb‐Hf isotopic characteristics and ubiquitous intermediate and felsic volcanic detritus in these rocks indicate rapid sediments accumulation sourced from a proximal magmatic terrane in a suprasubduction zone environment. The Paleozoic zircon U‐Pb age peaks from this study are comparable to those for the Permian arc‐related sediments along the Solonker Suture Zone, thus linking the Alxa active margin with the northern margin of the North China Craton during Middle‐Late Permian times. Our study thus provides key constraints for the final subduction processes of the PAO, documented within the ATB, before the terminal amalgamation of the southern Central Asian Orogenic Belt. Key Points: Syndepositional volcanism and tectonism exist within Permian volcano‐sedimentary rocks in the southwestern Alxa Tectonic Belt Sedimentological, compositional, and zircon U‐Pb‐Hf isotopic data point to a subduction zone setting in Alxa area until Late Permian Permian subduction and accretion processes existed along the southern Central Asian Orogenic Belt